(untitled) (Contemporary Journal of Social Science Review, 2025)
This study examines Jean Baudrillard’s concept of Hyperreality and consumerism in two culturally and geographically distinct novels: Klara and the Sun by Kazuo Ishiguro and Waste Tide by Chen Qiufan. Using Catherine Belsey’s model of textual analysis, the research highlights the divergent ways in which hyperreality is represented. In Ishiguro’s narrative, Hyperreality is embodied through Klara, whose simulated existence nonetheless conveys hope, empathy, and love, suggesting a humanizing potential within artificiality. By contrast, Qiufan’s Waste Tide depicts Hyperreality as a destructive force, dehumanizing individuals through Mimi’s transformation from “waste girl” into a fragmented, cybernetic being. Despite these contrasting portrayals, both texts foreground consumerism as the underlying force shaping human identity and struggle. Ultimately, the study argues that while Ishiguro’s vision of hyperreality culminates in peaceful acceptance of obsolescence, Qiufan’s novel critiques technological consumerism as a brutal system that reconfigures subjectivity. These comparative findings contribute to contemporary debates on posthuman identity, environmental degradation, and the cultural politics of consumerism.